Dike Propagation During Global Contraction: Making Sense of Conflicting Stress Histories on Mercury - Crane, Kelsey; Bohanon, Allison (Frontiers in Earth Science, 2021)
Thrust fault-related landforms, smooth plains units, and impact craters and basins have all been observed on the surface of Mercury. While tectonic landforms point to a long-lived history of global cooling and contraction, smooth plains units have been inferred to represent more punctuated periods of effusive volcanism. The timings of these processes are inferred through impact cratering records to have overlapped, yet the stress regimes implied by the processes are contradictory. Effusive volcanism often produces flood basalts through dikes, the propagation of which is dependent on being able to open and fill vertical tensile cracks when horizontal stresses are small. On the contrary, thrust faults propagate when at least one horizontal stress is very large relative to the vertical compressive stress. We made sense of conflicting stress regimes through modeling and Earth analogue work. We used frictional faulting theory to calculate stress relationships for tensile cracks and thrust faults. Using these stress relationships, we calculated deviatoric stresses during volcanism and thrust faulting. Deviatoric stresses were applied to test a physical model for dike propagation distance in the horizontally compressive stress regime of the Columbia River Flood Basalt Province, an Earth analogue for Borealis Planitia, the northern smooth plains, of Mercury. By confirming that dike propagation distances from sources observed in the province can be generated with the physical model, we confidently apply the model to confirm that dikes on Mercury can propagate in a horizontally compressive stress regime and calculate the depth to the source for the plains materials. Results imply that dikes could travel from ~89 km depth and that Mercury’s lithosphere is mechanically layered, with only the uppermost layer being weak.